Pentingnya pendaftaran tanah untuk pertama kali dalam rangka perlindungan hukum kepemilikan sertifikat tanah - Lisnadia Nur Avivah; Sutaryono Sutaryono; Dwi Wulan Titik Andari (Sekolah Tinggi Pertanahan Nasional, 2022)
To ensure legal certainty of land rights, land registration activities are carried out which are a series of land administration activities in collecting and processing physical and juridical data. The purpose of this study is to analyze the importance of the first land registration. The research method uses a normative juridical with a statutory approach. The results of this study indicate that to increase public interest in registering their land is to socialize about the benefits of the importance of land registration held by the government and non-government institutions. The reluctance of the community to register their land is caused by their assumptions about several things, namely the difficult procedure, the high costs associated with the taxes paid, the registration process is long and tends to be considered convoluted. It is necessary to disseminate more complete, clear and massive information about the importance of guaranteeing legal certainty over land right.